2017
DOI: 10.5114/amscd.2017.70600
|View full text |Cite
|
Sign up to set email alerts
|

Success or failure of non-invasive positive pressure ventilation in children with acute respiratory failure. Could it be predicted?

Abstract: <b>Introduction: </b> Noninvasive ventilation (NIV) has been developed to reduce complications associated with invasive ventilation (IV). Failure of NIV and delay in endotracheal intubation can increase patients’ morbidity and mortality. Thus early determination of patients who are unlikely to benefit from NIV is crucial for their management. We aimed in this study to identify the early predictors of success of NIV in children with acute respiratory failure (ARF).<br /> <b>Material and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Although we have three statistically significant predictors by multivariate logistic regression, the predictor with the largest OR is grade of RDS, followed by MAP and antenatal steroid use having the smallest effect with an OR of 1.09. A study in older children with respiratory failure also identified two comparable criteria as predictors for NIV success: MAP change and baseline degree of illness [33]. A possible limitation of our study is that the failure group was small, with only 12 patients, and therefore did not allow for extraction of other potential predictors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we have three statistically significant predictors by multivariate logistic regression, the predictor with the largest OR is grade of RDS, followed by MAP and antenatal steroid use having the smallest effect with an OR of 1.09. A study in older children with respiratory failure also identified two comparable criteria as predictors for NIV success: MAP change and baseline degree of illness [33]. A possible limitation of our study is that the failure group was small, with only 12 patients, and therefore did not allow for extraction of other potential predictors.…”
Section: Discussionmentioning
confidence: 99%
“…Other predictive factors that have been reported in the literature for pediatric NIV but were not included in this study are a higher PaO 2 /FiO 2 before NIV [33], hemodynamic response to NIV for success and a higher PaCO 2 for failure [34], low pH immediately after initiation of NIV as a predictor of failure [35], respiratory rate prior to NIV (James et al .) and the number of failing organs [36].…”
Section: Discussionmentioning
confidence: 99%
“…Both mother and child were treated favorably. This case report highlighted a prolonged latency period of TB infection, emphasizing the need for urgent treatment of neonates in such situations [21], especially taking into account pediatric acute respiratory failure [22].…”
Section: Discussionmentioning
confidence: 90%
“…The effect size of association between each of the studied SNPs and OS was quantified by hazard ratio (HR) adjusted according to the above-mentioned factors. Candidate predictors included in multivariable Cox regression models were significant univariate predictors along with all important clinical variables [23], so that the number of predictors (p) was lower than m/15, where m was the number of deaths in the studied sample [24]. Statistical analysis was performed using the advanced environment for statistical computing R version 3.4.4.…”
Section: Discussionmentioning
confidence: 99%